Incorporation Of Enzymatically Treated Stabilised Rice Bran In Butter Cookies: A Study On Physical, Textural And Rheological Properties - Soon, Yong Qi (Universiti Sains Malaysia, 2021)
The trend of people eating healthy food is increasing and they are looking for food that can be modified according to their nutrition needed. Enzymatically treated stabilised rice bran (ESRB) is a potential functional ingredients in baking product as it will provide better functional and nutritional benefits compared to raw rice bran and thermally stabilised rice bran. The objective of this research is to study the effects of enzymatically treated stabilised rice bran incorporation on the physical, textural and rheological quality of butter cookies. To achieve this objective, rheological analysis (dynamic oscillatory test) and texture profile analysis were done on all cookie dough formulations, whereas physical analysis (colour, density and spread ratio) and texture analysis (hardness and fracturability) were done on all cookie formulations (10%, 20% ,30% and 40% of ESRB was used to substitute wheat flour in butter cookies formulation). Results shown that different percentage of ESRB had a significant effect on the rheology, hardness and cohesiveness of dough as well as colour values and texture of cookies. Rheological properties (storage modulus and loss modulus) of cookie doughs had an increasing trend from ESRB 0% to ESRB 20%. In TPA, with increasing percentage of ESRB, hardness of cookie doughs increased significantly, whereas cohesiveness of cookie doughs decreased significantly. In term of physical properties, ESRB had a significant effect on the colour values (L* and b*) of cookies. Last but not least, an increasing amount of ESRB incorporated also had significantly increased the hardness of cookies. Therefore, the percentage of up to 20% of ESRB can be added into cookies is suggested as the colour of cookies formulations higher than ESRB 30% (as shown in Figure 4.10) will be obviously darker than control (ESRB 0%) which yielded cookies with undesirable appearance.